2012
DOI: 10.4318/tjg.2012.0538
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated interferon-based treatment in patients with advanced liver disease due to chronic delta hepatitis

Abstract: Amaç: ‹leri delta hepatitinde interferonlar›n güvenilirlik ve etkinli¤i araflt›r›lmam›flt›r. Çok merkezli bir klinik çal›flman›n bu alt analizinin amac›, kronik delta hepatitine ba¤l› ileri karaci¤er hastal›¤› olan ve ileri hastal›¤› olmayan hasta gruplar›n›, 48 haftal›k interferon alfa-2a (180 μgAnahtar kelimeler: Siroz, hepatitis delta, pegile interferon, tedavi Background/aims: The safety and efficacy of interferons in advanced delta hepatitis have not been explored. The aim of this subanalysis of a multic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
3
12
0
1
Order By: Relevance
“…5 Waiting for novel therapies, 6 peginterferon alfa remains the best option 7 , albeit its efficacy is limited 8 and there is no consensus about its duration. 9 Our experience strengthens the idea of very prolonged treatment with peginterferon alfa in selected patients, that is, those able to tolerate the therapy, even those with advanced compensated liver disease, 10 and when close monitoring of biochemical and virological parameters is feasible.…”
supporting
confidence: 57%
“…5 Waiting for novel therapies, 6 peginterferon alfa remains the best option 7 , albeit its efficacy is limited 8 and there is no consensus about its duration. 9 Our experience strengthens the idea of very prolonged treatment with peginterferon alfa in selected patients, that is, those able to tolerate the therapy, even those with advanced compensated liver disease, 10 and when close monitoring of biochemical and virological parameters is feasible.…”
supporting
confidence: 57%
“…Extending the duration of Peg-IFN therapy has shown no effect on response rate [49]. In a study from Turkey, 32 % of patients with advanced chronic liver disease achieved virological response with Peg-IFN treatment and there was no significant difference in treatment response between patients with advanced and non-advanced chronic liver disease [50]. Acute HDV hepatitis has been more challenging to treat.…”
Section: Treatmentmentioning
confidence: 99%
“…Although some studies reported that interferon treatment can be safely used in patients with compensated cirrhosis (38), decompensation might develop during the treatment.…”
Section: Contraindications Side Effects and Monitorization Of Pegifnmentioning
confidence: 99%